Board characteristics and financial reporting quality in Nigeria: the moderating effects of big 4 and audit tenure - Samuel, Eyenubo Akpovwre (2020)
Accounting and auditing practices in Nigeria suffer from institutional weaknesses in terms of regulations, compliance, and enforcement of standards that resulted to poor financial reporting quality on firms in Nigeria. Literature review reveals the missing link between board characteristics and financial reporting quality. Based on this gap this research attempts to examine the relationship between board characteristics, audit quality, and financial reporting quality. Moreover, the moderating effect of audit quality has been examined to further explain the financial reporting quality in Nigeria. Secondary data collected from the annual reports over the period 2011-2015. Multiple regression analysis employed to determine the effect of the focal variables indicating that audit committee size, and audit committee expertise have a positive and significant impact on financial reporting quality. However, board independence is significantly negative. Furthermore, the results reveal a statistically significant association of the interaction of auditor tenure and Big 4 with board characteristics and financial reporting quality. The audit tenure positively moderates audit committee expertise and negatively moderates board independence, audit committee diligence, and audit committee size and financial reporting quality. Furthermore, Big 4 positively moderates block shareholding and negatively moderates audit committee diligence and financial reporting quality. This indicates that the Big 4 and auditor tenure have a monitoring ability in mitigating and thus, enhancing financial reporting quality of Nigerian listed firms. In addition, the result reveals that director shareholding and audit committee independence are either vain or less active in controlling the management to ensure high-quality reports. Theoretically, this study indicates that board characteristics possess the monitoring ability that could enhance financial reporting quality. In addition, it highlights that the high audit quality and board characteristics exert influence on financial reporting quality. The results have valuable practical implications for stakeholders, the board of directors, company management and researchers.